Profile of a Romanian Rural School Leader and their Influence on Teacher Efficacy - Adina-Roxana Baștea; Horațiu Catalano; Crina Puie (Educaţia 21)
This study explores the characteristics of authentic school leaders in rural Romania and their impact on teacher efficacy. Rural schools in Romania face distinct challenges, including limited resources, socio-economic constraints, and difficulties in attracting and retaining qualified staff. Understanding how leaders navigate these obstacles to create a supportive educational environment is critical. The research addresses key questions: How do rural school leaders exhibit qualities such as transparency, ethics, efficacy, and self-awareness? What impact do these qualities have on teacher efficacy and professional growth? Data was gathered through surveys assessing leadership practices from the perspectives of both school leaders and their evaluators, considering different stages of teachers' professional practice (PP) and professional development (PD). The analysis revealed notable patterns, such as higher self-awareness among entry-level teachers and significant efficacy reported by mid-level teachers and those with 'gradul II' certification. These findings indicate a complex relationship between leadership practices and stages of teacher development. A significant observation was the disparity in transparency scores between 'gradul I' teachers and those with over 25 years of experience, suggesting areas for further research. Additionally, lower scores in ethics and efficacy among entry-level teachers point to the need for targeted support and development initiatives. The study highlights the critical role of authentic leadership in rural schools and offers insights into how effective leadership practices can strengthen teacher efficacy. By identifying strategic areas for improvement, the research provides valuable guidance for policymakers and educators working in challenging educational contexts.